Predicative possession choice in Argentinian Spanish - Martin Fuchs; Kendra Dickinson; Scott Schwenter (Isogloss)
This study investigates the expression of predicative possession in Argentinian Spanish, focusing on the alternation between two constructions: tener (‘have’) + NP and estar con (‘be with’) + NP. Building on previous research, we explore the factors that determine speakers’ choices between these constructions, particularly the influence of temporal context and the presence of adverbs. Using a forced-choice experimental design, participants were presented with vignettes varying in temporal duration (durative vs. non-durative) and adverbial modification (extending, limiting, or none). Results show a strong overall preference for the tener + NP construction, particularly in durative contexts. However, the estar con + NP construction is more likely to be selected in non-durative contexts, especially when a limiting adverb is present. These findings suggest that the distinction between the two constructions is not purely semantic but also pragmatically modulated by temporal and contextual factors. We argue that this pattern reflects a subset-superset relationship between the two constructions, where tener + NP can cover a broader temporal scope than estar con + NP. This overlap mirrors cross-linguistic findings on possessive constructions and aspectual distinctions, with implications for understanding grammaticalization processes in Romance languages.